(untitled) (Annals of Medical Research, 2025)
Aim: We aimed to isolate and characterize Kumquat-derived exosome-like nanovesicles (KNVs) and evaluate their potential therapeutic effects on colon cancer. Materials and Methods: KNVs were obtained by the ultracentrifugation method, and their purification was carried out by the sucrose density gradient ultracentrifugation method. The NTA method was used to measure the size distribution and particle concentration of KNVs. The BCA assay was utilized to determine the total protein concentrations of KNVs. MTT analysis was performed to examine the cytotoxic effects of KNVs against HCT 116 colon cancer cells. Results: Uniform and reproducible KNVs were successfully isolated. High yield and pure KNVs were obtained in the 30% sucrose layer after sucrose density gradient ultracentrifugation. NTA results showed that KNVs sizes were 153.1±1.0 nm and particle concentrations were 6.67 × 1012 particles/mL. The total protein concentration of KNVs were determined as 1,79 μg/μL. Cell viability results revealed that KNVs showed strong cytotoxic activity against HCT 116 cells in a concentration- and time-dependent manner. Furthermore, at a concentration of 20 μg/mL KNVs, HCT 116 cells showed a 50% reduction in cell viability in 48 hours. Conclusion: Consequently, our study shows that KNVs may hold promise as therapeutic candidates for the treatment of colon cancer in the future, and the research serves as a valuable resource for further research.